2020
DOI: 10.3390/jcm9051454
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Adhering to a Mediterranean Diet Supplemented with Extra Virgin Olive Oil and Pistachios in Pregnancy on the Health of Offspring at 2 Years of Age. Results of the San Carlos Gestational Diabetes Mellitus Prevention Study.

Abstract: The intrauterine environment may be related to the future development of chronic diseases in the offspring. The St. Carlos gestational diabetes mellitus (GDM) prevention study, is a randomized controlled trial that evaluated the influence of the early (before 12th gestational week) Mediterranean diet (MedDiet) on the onset of GDM and adverse gestational outcomes. Out of 874 women assessed after delivery (440 control group (CG)/434 intervention group (IG)), 703 children were followed (365/338; CG/IG), with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…As for the country of origin, 57.14% ( n = 8) ( 18 – 20 , 28 – 32 ) of the articles were carried out in Spain, two studies were carried out in the Netherlands (14.29%) ( 33 , 34 ), one in England (7.14%) ( 35 ), one in France (more specifically on the island of Guadeloupe) (7.14%) ( 36 ), one in the United States (7.14%) ( 37 ), and, finally, one that included participants from the United States, Greece, and Crete (7.14%) ( 21 ). In terms of design, of the 14 studies included, five were cohorts (35.71%) ( 21 , 33 , 34 , 36 , 37 ), four clinical trials (28.57%) ( 18 , 29 , 31 , 35 ), three cases and controls (21.43%) ( 24 , 30 , 32 ), and two were cross-sectional studies (14.29%) ( 19 , 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…As for the country of origin, 57.14% ( n = 8) ( 18 – 20 , 28 – 32 ) of the articles were carried out in Spain, two studies were carried out in the Netherlands (14.29%) ( 33 , 34 ), one in England (7.14%) ( 35 ), one in France (more specifically on the island of Guadeloupe) (7.14%) ( 36 ), one in the United States (7.14%) ( 37 ), and, finally, one that included participants from the United States, Greece, and Crete (7.14%) ( 21 ). In terms of design, of the 14 studies included, five were cohorts (35.71%) ( 21 , 33 , 34 , 36 , 37 ), four clinical trials (28.57%) ( 18 , 29 , 31 , 35 ), three cases and controls (21.43%) ( 24 , 30 , 32 ), and two were cross-sectional studies (14.29%) ( 19 , 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Following a MedDiet pre-pregnancy seems to be effective in preventing GDM and other maternofetal outcomes [ 147 ]. Compliance with MedDiet before the 12th gestational week was associated with a reduction of GDM [ 148 ] and with health benefits for the offspring, particularly in women with a pre-gestational BMI lower than 25 kg/m 2 and normal glucose tolerance [ 149 ]. It was proven that also a late first-trimester (>12 gestational weeks) degree of adherence to a MedDiet pattern seems to positively impact on a composite materno-fetal outcome (CMFCs) such as perineal trauma, emergency C-section, pre-eclampsia, pregnancy-induced hypertension, prematurity, and large or small-for-gestational-age (SGA).…”
Section: Mediterranean Diet For Prevention Of Obesity and Gestatiomentioning
confidence: 99%
“…3. Melero et al (93) Follow-up at 2-year post-partum. Primary endpoint: offspring health during first 2 years of life.…”
Section: San Carlos Gestational Diabetes Mellitus Prevention Study Madrid Spainmentioning
confidence: 99%
“…The supplemented Mediterranean diet reduced the incidence of GDM rate from 23⋅4 % (in the control group) to 17⋅1 % and improved maternal and neonatal outcomes (significantly lower rates of insulin-treated GDM, prematurity, emergency caesarean sections, perineal trauma and small and large for GA new-borns) ( 92 ) ( Table 5 ). Health benefits to the infant persisted during the first two years of life: the offspring of mothers receiving the supplemented Mediterranean diet during pregnancy had fewer hospital admissions requiring antibiotic and corticosteroid treatment, and fewer admissions related to asthma/bronchiolitis, especially in women with pre-gestational BMI <25 kg/m 2( 93 ) . A later sub-analysis of the data collected in the St. Carlos Gestational Diabetes Mellitus Prevention Study showed that mothers receiving the pistachio and EVOO-enriched diet had over 50 % lower risk of composite adverse maternofoetal outcomes, including lower mean fasting glucose and HbA levels, at 24–28th and 36–38th GW, in the intervention group compared to the standard care control group ( 94 ) .…”
Section: Glycaemic Control Beyond Energies: a Lesson From Pistachiosmentioning
confidence: 99%